2021
DOI: 10.18549/pharmpract.2021.3.2471
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy student-assisted medication reconciliation: Number and types of medication discrepancies identified by pharmacy students

Abstract: Background: Medication reconciliation aims to prevent unintentional medication discrepancies that can result in patient harm at transitions of care. Pharmacist-led medication reconciliation has clear benefits, however workforce limitations can be a barrier to providing this service. Pharmacy students are a potential workforce solution. Objective: To evaluate the number and type of medication discrepancies identified by pharmacy students. Methods: Fourth year pharmacy students completed best possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…The most common medication deviation type in our study were omissions, with the most commonly omitted medications being non-prescription. This is consistent with other studies that identified omissions [ 6 , 14 , 20 25 ] and vitamins/over-the-counter products [ 22 , 26 ] as the most common causes for medication deviations when a second in-person obtained BPMH is conducted against an initial in-person BMPH. This suggests that medications which were identified in the second, in-person, encounter, may be due to memory recall bias, as a result of prompting the patient multiple times, and not as a result of telepharmacy.…”
Section: Discussionsupporting
confidence: 92%
“…The most common medication deviation type in our study were omissions, with the most commonly omitted medications being non-prescription. This is consistent with other studies that identified omissions [ 6 , 14 , 20 25 ] and vitamins/over-the-counter products [ 22 , 26 ] as the most common causes for medication deviations when a second in-person obtained BPMH is conducted against an initial in-person BMPH. This suggests that medications which were identified in the second, in-person, encounter, may be due to memory recall bias, as a result of prompting the patient multiple times, and not as a result of telepharmacy.…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified that high-risk medication deviations were significantly associated with 'blood and blood forming organs' medications, which is consistent with literature [33,34]. Similarly, to other studies, the most common discrepancy type was drug omission [4,14,15,17,20,34,35]. Our study also identified that no-or-low-risk medication deviations were predominantly associated with non-prescription medications (e.g., vitamins, and "when needed" medications), which implies a difference between the pharmacist and the student's BPMH questioning process.…”
Section: Discussionsupporting
confidence: 91%